IMPROVING INTUITION SKILLS WITH REALISTIC MATHEMATICS EDUCATION - Hirza, Bonita; Kusumah, Yaya S.; Darhim, Darhim; Zulkardi, Zulkardi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
The intention of the present study was to see the improvement of studentsÃ¢â‚¬â„¢ intuitive skills. ThisÃ‚Â improvement was seen by comparing the Realistic Mathematics Education (RME)-basedÃ‚Â instruction with the conventional mathematics instruction. The subject of this study was 164Ã‚Â fifth graders of elementary school in Palembang. The design of this study was a Pretest-PosttestÃ‚Â Control Group Experiment. Data was analyzed with the help of SPSS. The result of this studyÃ‚Â showed that there was different improvement of studentsÃ¢â‚¬â„¢ skills. The improvement was higherÃ‚Â in the class using the RME-based instruction that in conventional mathematics class.Keywords: Realistic Mathematics Education (RME), IntuitionÃ‚Â DOI: http://dx.doi.org/10.22342/jme.5.1.1446.27-34